Pentoxifylline as add-on therapy in the treatment of moderate to severe psoriasis - Tanetsakunwatana, Trirat; Tovanabutra, Napatra; Kanchanarattanakorn, Kittika; Chiewchanvit, Siri (Biomedical Sciences and Clinical Medicine, 2023)
Background Psoriasis is a common chronic inflammatory skin disease in Thailand. It is incurable and can cause physical and psychological morbidity. Pentoxifylline has the ability to inhibit TNF-α synthesis and interleukin-1. which play a significant role in the pathogenesis of psoriasis. Objective To evaluate the efficacy and safety of pentoxifylline in patients with moderate to severe chronic plaque type psoriasis. Methods Patients with moderate to severe chronic plaque type psoriasis were enrolled in this prospective, open trial group study. They received oral pentoxifylline at 800 mg/day for eight weeks as add-on therapy. The primary end point was improvement of PASI 50 (defined as improvement of the psoriasis area and severity index ≥ 50% from baseline) at eight weeks post pentoxifylline treatment. Changes in itching score, global clinical status, and adverse effects also were evaluated. Results A total of 28 patients were studied, of which three were excluded, due to side effects and failure to follow-up. The mean PASI score of 25 patients, at week eight, showed significant improvement when compared to the baseline (7.08(±5.53) vs. 18.63(±9.33)) (p <0.001). The PASI 50 was achieved in 72.7% of the patients at week eight. The itching score was decreased significantly from the baseline (p=0.033). The global clinical status also was improved from the baseline. No serious or life threatening events were reported. Conclusion Pentoxifylline was shown to be an effective add-on therapy in the treatment of moderate to severe plaque type psoriasis. Larger and randomized controlled studies are needed to validate these results.